Long-acting recombinant human follicle-stimulating hormone (SAFA-FSH) enhances spermatogenesis - Kim, Daham; Lee, Soohyun; Cho, Yoon Hee; Kang, Min Jeong; Ku, Cheol Ryong; Chi, Hyunjin; Ahn, Jungsuk; Lee, Kyungsun; Han, Jaekyu; Chi, Susan; Song, Moo Young; Cha, Sang-Hoon; et al. (Frontiers in Endocrinology, 2023)
Administration of follicle-stimulating hormone (FSH) has been recommended to stimulate spermatogenesis in infertile men with hypogonadotropic hypogonadism, whose sperm counts do not respond to human chorionic gonadotropin alone. However, FSH has a short serum half-life requiring frequent administration to maintain its therapeutic efficacy. To improve its pharmacokinetic properties, we developed a unique albumin-binder technology, termed “anti-serum albumin Fab-associated” (SAFA) technology. We tested the feasibility of applying SAFA technology to create long-acting FSH as a therapeutic candidate for patients with hypogonadotropic hypogonadism. SAFA-FSH was produced using a Chinese hamster ovary expression system. To confirm the biological function, the production of cyclic AMP and phosphorylation of ERK and CREB were measured in TM4-FSHR cells. The effect of gonadotropin-releasing hormone agonists on spermatogenesis in a hypogonadal rat model was investigated. In in vitro experiments, SAFA-FSH treatment increased the production of cyclic AMP and increased the phosphorylation of ERK and CREB in a dose-dependent manner. In animal experiments, sperm production was not restored by human chorionic gonadotropin treatment alone, but was restored after additional recombinant FSH treatment thrice per week or once every 5 days. Sperm production was restored even after additional SAFA-FSH treatment at intervals of once every 5 or 10 days. Long-acting FSH with bioactivity was successfully created using SAFA technology. These data support further development of SAFA-FSH in a clinical setting, potentially representing an important advancement in the treatment of patients with hypogonadotropic hypogonadism.